2022
DOI: 10.3390/nu14142890
|View full text |Cite
|
Sign up to set email alerts
|

Does Food Intake of Australian Toddlers 12–24 Months Align with Recommendations: Findings from the Australian Feeding Infants and Toddlers Study (OzFITS) 2021

Abstract: (1) Background: Food-based dietary guidelines promote population health and well-being through dietary patterns that reduce chronic disease risk while providing adequate energy and nutrients. In Australia, recommended dietary patterns based on servings per day from the five food groups—fruits, vegetables, cereals and grains, meats and alternatives, and dairy—have been developed for toddlers 1–2 years of age. However, no study has assessed the intake of the five food groups in this age group nationally. (2) Aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…OzFITS 2021 is the first study to compare the dietary intakes of Australian toddlers to the recommended servings of all five food groups (fruits, vegetables, dairy cereals and grains, and meat and meat alternatives) [ 16 ]. We found a mismatch between the number of recommended servings from each food group and the dietary intake of toddlers in our study [ 15 , 17 ]. Toddlers consumed twice as many fruit servings as recommended, and nearly all toddlers consumed discretionary foods, despite no allowance for these foods.…”
Section: Summary Of Key Findings and Implicationsmentioning
confidence: 99%
“…OzFITS 2021 is the first study to compare the dietary intakes of Australian toddlers to the recommended servings of all five food groups (fruits, vegetables, dairy cereals and grains, and meat and meat alternatives) [ 16 ]. We found a mismatch between the number of recommended servings from each food group and the dietary intake of toddlers in our study [ 15 , 17 ]. Toddlers consumed twice as many fruit servings as recommended, and nearly all toddlers consumed discretionary foods, despite no allowance for these foods.…”
Section: Summary Of Key Findings and Implicationsmentioning
confidence: 99%
“…The FITS studies that have been completed and published are shown in Table 1 [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These studies have been ongoing, and since 2002, there have been seven countries having published results, including the OzFITS studies now published in this Special Issue [ 4 , 5 , 6 , 7 , 8 ]. With each survey this is an opportunity to improve or modify the methodology yet stay consistent with a common analysis approach in more recent FITS such as those in Australia, China, Mexico, the Philippines, Russia, and the United States [ 3 , 4 ].…”
Section: Feeding Infants and Children Studies (Fits)mentioning
confidence: 99%
“…As shown in Table 1 , OzFITS is the latest FITS, and results are provided in four papers in this Special Issue [ 5 , 6 , 7 , 8 ] with a concluding paper [ 9 ]. These researchers indicated that national nutrition surveys conducted in Australia over the past 30 years had not included sampling of children under 2 years of age [ 5 ].…”
Section: The Australian Feeding Infants and Children Study (Ozfits)mentioning
confidence: 99%
See 2 more Smart Citations